Joint user association and interference mitigation for drone-assisted heterogeneous wireless networking - Chuan’an Wang (EURASIP Journal on Wireless Communications and Networking, 2019)
Abstract Using drone as aerial access point (AAP) to provide communication connectivity becomes an attractive application in future industrial wireless networking. However, the user association becomes more complex in the 3-tier drone-assisted heterogeneous networking (DAHN) due to the various types of APs. To address the issue, we formulated it as an association degree maximization problem, in which the load of APs and the user quality of service (QoS) rate requirement are considered. Since this is a non-linear mixed integer optimization problem, we relax the associated index variable and adopt the distributed heuristic method to find the near-optimal solution. Further, to mitigate the intra- and inter-layer interference, the coordinated multiple points (CoMP) supporting approach for edge user is used for enhancing the service performance. Simulations show that the proposed scheme provides better performances with a significant complexity reduction.